Comparative analysis of methods for determination of supply flows - Semchenko, N. О.; Kholodova, O. О.; Buhaiova, M. О.; Семченко, Н. О.; Холодова, О. О.; Бугайова, М. О. (Харківський національний автомобільно-дорожній університет, 2021)
Problem. The capacity of signalized intersections is determined using the concept of "saturation flow". It is the main characteristic in the process of their analysis, design and calculation. The work is devoted to solving the scientific-applied problem of increasing the efficiency of the signalized intersection at one level by choosing a rational method of determining saturation flows for these characteristics of traffic flows, geometric parameters of the intersection and infrastructure in its area. The subject of the study is the influence of the main characteristics of the traffic flow, parameters and infrastructure of the intersection on the saturation flow value. Goal. The aim of the work is the analysis of the influence of the main characteristics of the traffic flow, parameters and infrastructure of the intersection on the saturation flow value. Methodology. The calculation of the control regime at the intersection is based on determining the relation between the traffic intensity of vehicles at the intersection and the saturation flow value, which changes under the influence of a number of factors. Analytical calculation of the saturation flow value is based on using of correction factors that take into account the influence of these factors. Results. The methods of determination of saturation flows are analyzed out in the work; performed a comparative analysis of the definition of ideal saturation flows by different methods; a comparative analysis of the determination of the saturation flow correction coefficients for the parameters that have an effect on it were performed; the estimation of discrepancy at calculations of coefficients of correction of saturation flows by various methods is done; the list of coefficients which need to be considered at definition of their influence on a saturation flow is refined. Originality. In oppose to classical and other approaches to determining the saturation flow, the method recommended by the American "Highway Capacity Manual" takes into account more parameters of influence. It is proposed to use this method for the saturation flow calculation, but with an updated list of coefficients that must be taken into account in the calculations. Practical value. The results of the work can be used in the practice of improving the efficiency of signalized intersections in sections of the urban road network, as well as in further research on this topic.
Порівняльний аналіз методів визначення потоків насичення
Keywords: saturation flow; signalized intersection; urban road network; method; потік насичення; регульоване перехрестя; вулично-дорожня мережа; метод; 656.13; 10.30977/AT.2219-8342.2021.48.0.64